The geological setting of Carboniferous magmatism in the proto-Andean margin of Gondwana, Sierra Pampeanas, Argentina - Dahlquist, J. A. (2014)
Fil: Dahlquist, J. A. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.